Assessment of TSH, FT4 and TPO-Ab Status During 1st Trimester of Pregnant Women in Dhaka City - Banik, Shyamal Chandra; Yeasmin, Tahmina; Ahmed, Farjana; Towhid, Ferdous; Chowdhury, Arifuzzaman; Ullah, Mohib (Journal of Dhaka National Medical College & Hospital, 2020)
Background: Thyroid dysfunction may occur in pregnancy. Objective: To measure serum TSH, FT4 & TPO-Ab levels during 1st trimester of normal pregnant women. Method: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from July 2016 to June 2017. The ethical permission was taken from Institutional Ethics Committee (IEC) of SSMC. Total 60 female subjects, age ranged from 20 to 35 years were included in this study, among them 30 were apparently healthy pregnant women of 1st trimester (study group) and 30 were apparently healthy non-pregnant nulliparous women (control group). Serum TSH, FT4 and TPO-Ab levels were measured. The statistical analysis was done by Unpaired t-test. Results: In this study, mean serum TSH level was significantly (p<0.01) lower and serum FT4 level was significantly (p<0.01) higher in 1st trimester than that of non-pregnant group. However, among the 1st trimester of pregnant women 13.33% were TPO-Ab positive and 10% were subclinical hypothyroid (SCH). Conclusion: The present study reveals that subclinical hypothyroidism occurs in 1st trimester of pregnant women. So, thyroid screening should be done routinely during this period. J. Dhaka National Med. Coll. Hos. 2020; 26 (02): 06-09